Multicultural Islamic Education Curriculum and Social Cohesion: Negotiating Religious Identity in Diverse Communities - Azmira, Tahani (Universitas Muhammadiyah Surakarta, 2026)
The increasing intensity of social polarization, digital radicalization, and identity-based conflict within multicultural societies has raised urgent concerns regarding the role of Islamic education in promoting social cohesion and intercultural coexistence. Despite the growing discourse on multicultural education, limited studies have critically examined how multicultural Islamic education curricula negotiate religious identity while simultaneously fostering inclusive citizenship within diverse communities. This study aims to explore the role of multicultural Islamic education curriculum in shaping religious identity negotiation and strengthening social cohesion in Indonesia and Morocco. Employing a qualitative multi-site comparative design, the research involved 80 participants consisting of educators, curriculum specialists, students, religious leaders, and community representatives across several educational institutions in both countries. Data were collected through semi-structured interviews, classroom observations, and document analysis, and analyzed using thematic analysis. The findings reveal that multicultural Islamic education functions as a transformative pedagogical framework that enables students to maintain religious commitment while developing intercultural competence, ethical inclusivity, and democratic engagement. The study further demonstrates that dialogical pedagogy, peace-oriented curriculum practices, and community-based learning significantly contribute to reducing exclusivist attitudes and strengthening social cohesion. However, the research also identifies persistent challenges, including ideological resistance, limited teacher competence, and the growing influence of digital polarization on students’ religious perceptions. The study argues that reconstructing Islamic education requires not only curriculum reform but also broader epistemological transformation integrating critical pedagogy, digital literacy, and ethical citizenship. These findings contribute to contemporary debates on multicultural education, Islamic pedagogy, and social cohesion in increasingly plural and digitally mediated societies.